Geometric-Gamma Collective Modified Value-at-Risk Model in Life Insurance Risk - Iqbal Al-Banna Ismail, Muhammad; ., Sukono; Talib BIN Bon, Abdul; Hidayat, Yuyun; Lesmana, Eman; Supian, Sudradjat (International Journal of Engineering and Technology, 2018)
Claim risk is a payment made by the insurance company to the policyholder. Actuaries in insurance companies should be able to measure and control the risk of claims, in order to avoid losses to insurance companies. In this paper we analyze the Geometric-Gamma Collective Modified Value-at-Risk model in life insurance risk. In this research, there is a development of claim risk measure called Collective Modified Value-at-Risk, which is an extension of Collective Risk model. This Collective Modified Value-at-Risk model requires estimation of the mean, variance, skewness, and kurtosis parameters. The result of this research, is that the extent of this model can be applied to the risk of claims amount of non-normal distributed. Thus, the Collective Modified Value-at-Risk model can serve as one of the statistical alternatives for measuring the risk of claims on life insurance.Â Â